Low noncarbonic buffer power amplifies acute respiratory acid-base disorders in patients with sepsis: an in vitro study - Langer, Thomas; Brusatori, Serena; Carlesso, Eleonora; Zadek, Francesco; Brambilla, Paolo; Ferraris Fusarini, Chiara; Duska, Frantisek; Caironi, Pietro; Gattinoni, Luciano; Fasano, Mauro; Lualdi, Marta; Alberio, Tiziana; et al. (Journal of applied physiology (Bethesda, Md., 2021)
Patients with sepsis have typically reduced concentrations of hemoglobin and albumin, the major components of noncarbonic buffer power (β). This could expose patients to high pH variations during acid-base disorders. The objective of this study is to compare, in vitro, noncarbonic β of patients with sepsis with that of healthy volunteers, and evaluate its distinct components. Whole blood and isolated plasma of 18 patients with sepsis and 18 controls were equilibrated with different CO2 mixtures. Blood gases, pH, and electrolytes were measured. Noncarbonic β and noncarbonic β due to variations in strong ion difference (βSID) were calculated for whole blood. Noncarbonic β and noncarbonic β normalized for albumin concentrations (βNORM) were calculated for isolated plasma. Representative values at pH = 7.40 were compared. Albumin proteoforms were evaluated via two-dimensional electrophoresis. Hemoglobin and albumin concentrations were significantly lower in patients with sepsis. Patients with sepsis had lower noncarbonic β both of whole blood (22.0 ± 1.9 vs. 31.6 ± 2.1 mmol/L, P < 0.01) and plasma (0.5 ± 1.0 vs. 3.7 ± 0.8 mmol/L, P < 0.01). Noncarbonic βSID was lower in patients (16.8 ± 1.9 vs. 24.4 ± 1.9 mmol/L, P < 0.01) and strongly correlated with hemoglobin concentration (r = 0.94, P < 0.01). Noncarbonic βNORM was lower in patients [0.01 (-0.01 to 0.04) vs. 0.08 (0.06-0.09) mmol/g, P < 0.01]. Patients with sepsis and controls showed different amounts of albumin proteoforms. Patients with sepsis are exposed to higher pH variations for any given change in CO2 due to lower concentrations of noncarbonic buffers and, possibly, an altered buffering function of albumin. In both patients with sepsis and healthy controls, electrolyte shifts are the major buffering mechanism during respiratory acid-base disorders.NEW & NOTEWORTHY Patients with sepsis are poorly protected against acute respiratory acid-base derangements due to a lower noncarbonic buffer power, which is caused both by a reduction in the major noncarbonic buffers, i.e. hemoglobin and albumin, and by a reduced buffering capacity of albumin. Electrolyte shifts from and to the red blood cells determining acute variations in strong ion difference are the major buffering mechanism during acute respiratory acid-base disorders.
Keywords: Hydrogen-Ion Concentration; electrolytes; poruchy acidobazické rovnováhy; sepse; Sepsis; acidosis, respiratory; lidé; Acid-Base Imbalance; sepsis; analýza krevních plynů; kyseliny; buffers; acid-base equilibrium; Acid-Base Equilibrium; Blood Gas Analysis; acidobazická rovnováha; koncentrace vodíkových iontů; Acids; Humans